2011
DOI: 10.1111/j.1467-8624.2011.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Acuity of the Approximate Number System Underlies Mathematical Learning Disability (Dyscalculia)

Abstract: Many children have significant mathematical learning disabilities (MLD, or dyscalculia) despite adequate schooling. We hypothesize that MLD partly results from a deficiency in the Approximate Number System (ANS) that supports nonverbal numerical representations across species and throughout development. Here we show that ninth grade students with MLD have significantly poorer ANS precision than students in all other mathematics achievement groups (low-, typically-, and high-achieving), as measured by psychophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
506
4
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(559 citation statements)
references
References 42 publications
34
506
4
15
Order By: Relevance
“…Significantly, the correspondence between a number's name or symbol and the quantity represented is, essentially, a human invention requiring instruction (Geary 2013). Children who have difficulty with this mapping process tend to experience later mathematical difficulties (Kroesbergen et al 2009;Mazzocco et al 2011).…”
Section: Awareness Of the Relationship Between Number And Quantitymentioning
confidence: 99%
“…Significantly, the correspondence between a number's name or symbol and the quantity represented is, essentially, a human invention requiring instruction (Geary 2013). Children who have difficulty with this mapping process tend to experience later mathematical difficulties (Kroesbergen et al 2009;Mazzocco et al 2011).…”
Section: Awareness Of the Relationship Between Number And Quantitymentioning
confidence: 99%
“…Later on, the influence of parallel surface processing decreases (Rousselle & Noël, 2008) but even adults continue to be sensitive to perceptual dimensions in their numerical judgments (Gebuis & Reynvoet, 2012a, 2012bSzucs, Nobes, Devine, Gabriel, & Gebuis, 2013). Even if the majority of studies currently try to control the influence of perceptual variables when assessing non-symbolic magnitude processing Halberda, Mazzocco, & Feigenson, 2008;Mazzocco, Feigenson, & Halberda, 2011;Piazza et al, 2010;Piazza, Izard, Pinel, Le Bihan, & Dehaene, 2004), the visual stimulus properties (e.g., surface, density) cannot be controlled for in each individual trial (Gebuis & Reynvoet, 2011, 2012a.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that individuals' ANS acuities are correlated with achievement in symbolic mathematics (e.g. Gilmore, McCarthy & Spelke, 2010;Libertus, Feigenson & Halberda, 2011;Mazzocco, Feigenson & Halberda, 2011a, 2011b; but see Inglis, Attridge, Batchelor & Gilmore, 2011;Price, Palmer, Battista & Ansari, 2012), lending credence to the suggestion that the ANS is implicated in the development of symbolic mathematics competence.…”
mentioning
confidence: 86%